(untitled) (EAAE Annual Conference Proceedings, 2023)
The creation of the New European Bauhaus indicates how crucial architects and designers are to take meaningful action in an era marked by the SDGs. Architectural archives provide an excellent field to learn from particular interpretations on how to relate to the built environment. Despite its potential as a valuable tool for research, archives are often disregarded in architectural education, vacating their understanding and interpretation to art and architecture historians.